Polysaccharide capped antibacterial silver nanoparticles synthesis using green chemistry. (26th May 2020) - Sarkar, Joy; Maity, Gajendra Nath; Khatua, Somanjana; Mondal, Soumitra; Acharya, Krishnendu
Advancement of an environment friendly, trustworthy, and speedy route for the production of Ag-NP using natural system is an essential urge in nanotechnology. Biological synthetic techniques are considered as a better alternative over other conventional methods. Silver is a safe inorganic element that is projected as 'next-gen' antimicrobial agent and had been extensively used against several bacterial strains from the ancient times. Here, we document a low-cost green synthesis approach for construction of Ag-NP using fruit extracted polysaccharide of Bruguiera cylindrica, a mangrove plant of Sundarban. During the investigation of GC-MS an adequate amount of glucose was found as major carbohydrate molecule in the extracted polysaccharide. Synthesised Ag-NP were also characteristically described by UV-Vis, DLS, TEM, EDAX, XRD and FTIR. The average diameter of the Ag-NP was 4.5 ± 1 nm. Additionally, antibacterial nature of Ag-NP was also find out against some of the pathogenic gram-positive and gram-negative bacteria.